Winter wishes! - Depken, Kristen L; Aikins, Dave; Random House Children's Books; Viacom International (New York Random House, 2017)
When Nickelodeon's Shimmer and Shine accidentally bring home two mischievous ice sprites, the twin genies must return the sprites before their palace becomes a winter wonderland! Boys and girls ages 4 to 6 will love this Step 2 deluxe Step into Reading leveled reader based on Nickelodeon's Shimmer and Shine that features over 30 shiny stickers. A perfect holiday or winter read! Step 2 Readers use basic vocabulary and short sentences to tell simple stories. For children who recognize familiar words and can sound out new words with help. Boom Zahramay! Join the madcap, magical adventures of genie-in-training twin sisters Shimmer and Shine as they grant wishes for their best human friend Leah and show preschoolers that things are always better when you work together. --Publisher
At head of title: Nickelodeon Shimmer and Shine
Preschool-Grade 1
2
Keywords: JUVENILE FICTION / Girls & Women; JUVENILE FICTION / Media Tie-In; JUVENILE FICTION / Social Themes / Friendship; Jinn -- Juvenile fiction; Jinn; Twin sisters -- Juvenile fiction; Twin sisters; Wishes -- Juvenile fiction; Wishes; Genies -- Fiction; Sisters -- Fiction; Twins -- Fiction; Wishes -- Fiction; Wishes -- Fiction; Wishes -- Juvenile fiction; Fiction; Juvenile works; Readers (Publications); Readers (Publications); Early Reader